When women win: Can female representation decrease gender-based violence? - Verónica Frisancho Robles; Euē Pappa; Chiara Santantonio (Inter-American Development Bank (IDB), 2022)
Every day, three women are murdered in the United States by a current or former partner. Yet policy action to prevent gender-based violence has been limited. Previous studies have highlighted the effect of female political representation on crimes against women in the developing world. This paper investigates whether the election of a female politician reduces the incidence of gender-based violence in the United States. Using a regression discontinuity design on mixed-gender races, we find that the election of a female House Representative leads to a short-lived decline in the prevalence of femicides in her electoral district. The drop in femicides is mainly driven by a deterrence effect that results from higher police responsiveness and effort in solving gender-related crimes.
Keywords: D72; J12; J16; 330; Gender-related violence; Close elections; Police effort; Regression discontinuity